2001
DOI: 10.1159/000050515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Portable Recording Device (Somnocheck<sup>®</sup>) for Use in Patients with Suspected Obstructive Sleep Apnoea

Abstract: Background: Portable recording devices for the diagnosis of obstructive sleep apnoea (OSA) should be carefully evaluated before being used on a routine basis in out-patients. Objective: This study was designed to evaluate the diagnostic accuracy of the new portable recording device, Somnocheck® (SC). Methods: Nocturnal polysomnographies (PSG) and SC recordings were performed simultaneously in the sleep laboratory in 51 patients with suspected OSA, and were analysed manually by a blinded investigator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 7 publications
(7 reference statements)
2
26
0
1
Order By: Relevance
“…Excluding these patients, the bias of AHI was 0Ϯ12 h Ϫ1 . The measure of agreement between the 2 methods was 0.7 on statistics, which is similar to other home-based PSG recording systems [17][18][19] and satisfactory for clinical screening purposes and for monitoring treatment effects. The intraclass correlation coefficient of 0.73 indicates that 73% variation in apnea/hypopnea scores per 5-minute epoch during the entire sleep study was related to variation in reference PSG scores.…”
Section: Discussion Main Findingssupporting
confidence: 67%
“…Excluding these patients, the bias of AHI was 0Ϯ12 h Ϫ1 . The measure of agreement between the 2 methods was 0.7 on statistics, which is similar to other home-based PSG recording systems [17][18][19] and satisfactory for clinical screening purposes and for monitoring treatment effects. The intraclass correlation coefficient of 0.73 indicates that 73% variation in apnea/hypopnea scores per 5-minute epoch during the entire sleep study was related to variation in reference PSG scores.…”
Section: Discussion Main Findingssupporting
confidence: 67%
“…The only other study to examine the effect of CRT on CSR differed methodologically from the present study, in that the present study used comprehensive overnight, attended PSG, which monitored sleep, respiration, heart rate, PLM and body position, whereas the previous study used an ambulatory, nonattended, cardiorespiratory polygraph, which monitored respiration and heart rate alone [31,32], and has not been validated in patients with CSR. It is believed that PSG provides a more accurate estimation of apnoea frequency, reliably distinguishes obstructive and central events, which are likely to coexist in patients with heart failure, in addition to objectively monitoring sleep quality and identifying PLM.…”
Section: Limitations and Comparisons With Previous Datamentioning
confidence: 83%
“…However, different studies investigating the ability of polygraphy to detect sleep-disordered breathing showed a high diagnostic accuracy of the portable recording devices [42][43][44]. It is unlikely that the additional information on sleep stages given by polysomnography would profoundly modify the results.…”
Section: Limitationsmentioning
confidence: 99%